Who accepts bribery? Evidence from a global household survey - Johann Graf Lambsdorff (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2010)
This paper processes responses from households in 66 countries to address differences in the extent to which bribes and gifts are considered acceptable. Levels of acceptance differ substantially from one country to another, but they do not conform to popular expectations: Respondents in rich, western countries do not exhibit lower levels of acceptance. A higher acceptance of bribery can be observed in former colonies and those without a majority religion. Acceptance is higher among those who paid a bribe. Buddhists and less educated judge more situation-specific, accepting more often if they paid bribes themselves. Culture shapes attitudes towards bribery, but the western world fails to exhibit the expected moral rigor.
Keywords: D73; C83; 330; Civil Liberty; Colonialism; Corruption; Cognitive Dissonance; Moral Reasoning; Moral Superiority; Religion